Orientasi Pendidikan Berwawasan Kebangsaan - Hasyim, Farid (UIN Maulana Malik Ibrahim Malang, 2003)
Restoration and educational reform can be a moment of self-awareness as a nation of justice and equality issues. Sensitivity to economic and social inequalities should grow in the awareness of society, more so with an increasingly erratic atmosphere, and this moment will be useless if education is not directed to openness, critical nature and respect for the diversity of political, economic, social and culture of the true nation that is in accordance with the 1945 Constitution and the philosophy of the state and nation of Indonesia. Restorasi dan reformasi pendidikan bisa menjadi momen penyadaran diri sebagai bangsa akan masalah keadilan dan kesetaraan. Kepekaan terhadap kesenjangan ekonomi dan sosial seharusnya semakin tumbuh dalam kesadaran masyarakat , lebih-lebih dengan adanya suasana yang semakin tidak menentu, dan momen ini akan sia-sia bila pendidikan tidak diarahkan kepada keterbukaan, sifat kritis serta menghormati keanekaragaman struktur politik, ekonomi, sosial dan budaya bangsa yang benar yang sesuai dengan UUD 45 dan falsafah negara dan bangsa Indonesia.